(untitled) (Anclajes, 2020)
This article proposes a review of the concept of “rhetoric” postulated by the Group µ based on the notion of practice by Louis Althusser and the semiotic theory of Charles S. Peirce. In this framework, the rhetoric –or the rhetorical apprehension of a discourse– is understood not only as a dialectical overlap of degrees, but also as a transformation process that involves a raw material, a product and a transformation criterion. The focus of the article is on understanding how the transformation of certain discourses occurs when they enter the rhetorical process. From the analysis of contemporary poetic discourses –visual, sculptural, exhibition, among others–, we seek to demonstrate that the transformation made by a rhetorical discourse involves three kinds of interventions on their raw materials: a theoretical one –the ontological definition–, an economic one –the one related to its availability in a market of goods–, and a policy –its positioning in relation to the areas of belonging and regulation of these raw materials. The recognition of these interventions and the identification of the dominant instance can help characterize the material strategy in the rhetorical analysis of a discourse.